2021
DOI: 10.1038/s41598-021-95019-1
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based prediction of acute kidney injury after nephrectomy in patients with renal cell carcinoma

Abstract: The precise prediction of acute kidney injury (AKI) after nephrectomy for renal cell carcinoma (RCC) is an important issue because of its relationship with subsequent kidney dysfunction and high mortality. Herein we addressed whether machine learning (ML) algorithms could predict postoperative AKI risk better than conventional logistic regression (LR) models. A total of 4104 RCC patients who had undergone unilateral nephrectomy from January 2003 to December 2017 were reviewed. ML models such as support vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Traditional statistical models such as logistic regression analysis have been previously utilized to construct such prognostication tools [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In recent years, ML predictive algorithms have emerged as a method to handle high-dimensional, unstructured, and complex structured data including hospitalized patient with AKI [ 27 , 28 , 29 , 30 , 31 ]. While autoML has been shown to be very effective, with high predictive performance comparable to human hyperparameter optimization and with higher time-efficient workflow when compared to non-automated ML [ 41 , 43 ], autoML has never been utilized in the development of AKI prediction models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional statistical models such as logistic regression analysis have been previously utilized to construct such prognostication tools [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In recent years, ML predictive algorithms have emerged as a method to handle high-dimensional, unstructured, and complex structured data including hospitalized patient with AKI [ 27 , 28 , 29 , 30 , 31 ]. While autoML has been shown to be very effective, with high predictive performance comparable to human hyperparameter optimization and with higher time-efficient workflow when compared to non-automated ML [ 41 , 43 ], autoML has never been utilized in the development of AKI prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI) and machine learning (ML) have been increasingly applied to individualized medicine [ 21 , 22 , 23 , 24 , 25 , 26 ], including the prediction of AKI in various settings [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. ML algorithms can handle nonlinear, complex, and multidimensional data [ 36 , 37 ], and recent studies have shown high predictive performance from ML algorithms that outperform traditional statistical analyses [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“… 26 Our results are consistent with previous studies in more selected populations. 27 , 28 For example, a retrospective cohort study of 4104 renal cell carcinoma (RCC) patients in South Korea found that the application of ML algorithms improves the predictability of acute kidney injury after nephrectomy for RCC, and these models perform better than conventional logistic regression-based models. 27 …”
Section: Discussionmentioning
confidence: 99%
“…However, in another study performed in 2020 by Zhu et al (47), by incorporating preoperative, intraoperative and post-operative variables and using multiple methods to learn and train information on 87 patients, the results showed that the best performing XGBoost model had an AUC value of 0.749, which was lower than that of the classical logistic regression model of 0.826. It may be difficult to conduct parallel comparisons among the only three studies at present because of the degree of variation in the between-group design; for example, there was a certain proportion of RN patients among the 4,104 patients included in the first study (45), whereas the third study included all patients with isolated kidney (47). In addition, in a single study, differences in operator and surgical approaches (manual or robotic, laparoscopic or open) may also lead to confounding bias, making the accurate prediction of outcomes complex and difficult.…”
Section: Special Surgery-related Aki Prediction Modelmentioning
confidence: 99%